Strategi Komunikasi sosial Media Influencer Mikro "Uja (@syujaaja)" di Tiktok Dalam Membangun Minat Beli Konsumen - Irafani, Ganis El; Fadillah, Dani (Borobudur Communication Review, 2026)
This study was conducted to analyze the communication strategies of TikTok micro-influencer “Uja (@syujaaja)” in building consumer purchase intent on the TikTok social media platform. The study employed a qualitative descriptive approach using the netnography method during the period of August–October 2025. Data were collected through observation of TikTok content, documentation, and analysis of audience comments using SocialKit, which was selected for its ability to categorize comment sentiment into positive, negative, and neutral. The results indicate that communication strategies such as storytelling, leveraging TikTok trends, active engagement in the comments section, and utilizing the “yellow shell” feature can increase audience engagement and gradually shape purchase intent. Additionally, the interaction between the influencer and the audience demonstrates the presence of social influence, which plays a role in shaping the audience’s perceptions and interest in the promoted products. This study concludes that the communication strategies of micro-influencers on TikTok not only function as a digital promotional medium but also build emotional closeness and audience trust through interactive two-way communication.